2018
DOI: 10.3928/00220124-20180116-08
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Knowledge of Dutch Nursing Students and Hospital Nurses on Aging

Abstract: Throughout the nursing career, basic care topics in relation to care for older patients should play a key role in basic nursing education programs, as well as for continuing education programs provided in hospitals for nurses. J Contin Educ Nurs. 2018;49(2):84-90.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
5
15
0
Order By: Relevance
“…This study found significant differences in knowledge, attitudes, and negative ageism vary among nurse groups by selected sociodemographic/professional characteristics. Consistent with previous studies in other global regions (Dikken, Bakker, Hoogerduijn, & Schuurmans, 2018), nurses in this study had significantly low levels of knowledge about aging. However, the average score of nurses on the FAQ1 (11.80 of 25) in this study was even lower than scores obtained from previous Western and Eastern studies using the same tool (Deasey, Kable, & Jeong, 2018;Lan et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…This study found significant differences in knowledge, attitudes, and negative ageism vary among nurse groups by selected sociodemographic/professional characteristics. Consistent with previous studies in other global regions (Dikken, Bakker, Hoogerduijn, & Schuurmans, 2018), nurses in this study had significantly low levels of knowledge about aging. However, the average score of nurses on the FAQ1 (11.80 of 25) in this study was even lower than scores obtained from previous Western and Eastern studies using the same tool (Deasey, Kable, & Jeong, 2018;Lan et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…One of the most important limitation was the poor quality of measurement instruments used which was already noticed in the year 2000 [6], but no new instruments were adequately developed and validated between 2000 and 2013. Thereafter, Dikken et al developed and validated a new instrument, the Knowledge about Older Patients -Quiz (KOP-Q) [14,15] in order to investigate the knowledge levels about older patients among nursing student and hospital nurses [16]. The results from this study were in line with previous results from studies included by Courtney et al [6], Liu et al [7] and Rush et al [9]: a substantial proportion of participants in all groups demonstrated insufficient knowledge about older patients.…”
Section: Introductionsupporting
confidence: 81%
“…The results from this study were in line with previous results from studies included by Courtney et al [6], Liu et al [7] and Rush et al [9]: a substantial proportion of participants in all groups demonstrated insufficient knowledge about older patients. Because of methodological limitations encountered in previous studies [6,7], and a small number of participating hospitals and nurses included in the more recent studies regarding nurses' knowledge levels [16], the generalizability of results for the Netherlands can be questioned.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in the number of chronic diseases and co-morbidities enlightens the need to have more experienced and knowledgeable health-care providers to care for the growing numbers of chronically ill older adults (European Economic and Social Committee, 2013). However, evidence from the literature asserts that health-care providers including physicians, (Skirbekk and Nortvedt, 2014), medicine students (Singh et al, 2018), physical therapy students and nursing students (Dikken et al, 2018), hold with varying degrees, ageist attitudes toward older adults. Although nurses are in the first line to provide the best possible care for their patients, very few ageismrelated studies have been conducted among nurses caring for older adults.…”
Section: Introductionmentioning
confidence: 99%